Attention deficit hyperactivity disorder - symptoms, diagnosis and therapy among children and adults. - Surowiec, Agata; Dobko, Katarzyna; Frącz, Gabriela; Glac, Agata; Kuliga, Klaudia; Musz, Kinga; Sejnowska, Natalia; Socha, Agnieszka; Śnieżek, Kinga; Zając, Anna (Journal of Education, Health and Sport, 2023)
Introduction: The prevalence of Attention Deficit Hyperactivity Disorder (ADHD) in the world is estimated at about 5%. Among adults, it occurs with a frequency of 2.5%. This syndrome can significantly impair functioning in various areas of life. There is a treatment to reduce the symptoms. Aim of the study: The aim of the study was to collect and analyze publications on attention deficit hyperactivity disorder - symptoms, diagnosis and therapy, taking into account the differences among children and adults. Material and methods: We reviewed the literature available in the PubMed database using the keywords: "ADHD"; "Attention deficit hyperactivity disorder"; ’’ ADHD diagnosis’, ’’ADHD therapy’; ‘’ADHD drug therapy’, ‘’Methylphenidate’, ‘’Atomoxetine” Results: The clinical presentation of the disorder changes over the years. The main symptoms among children are related to inattention and impulsiveness, while among adults, hyperactivity can turn into a feeling of inner fear. Among children, frequent accompanying disorders are behavioral and oppositional-defiant disorders, and among adults, sleep disorders, personality, mood and anxiety disorders. ADHD treatment is based on a multimodal approach that uses cognitive behavioral therapy and effective stimulants (methylphenidate) and non-stimulants (atomoxetine) among children and adults. Conclusions: There are differences in symptoms, comorbidities and diagnosis of ADHD among children and adults. Pharmacotherapy is carried out using the same drugs that are safe and effective. Diagnosis of the disorder and both non-pharmacological and pharmacological help are important due to the risk of increased mortality in patients.